Early Rhythm-Control Therapy in Patients with Atrial Fibrillation - Kirchhof, Paulus; Camm, A. John; Goette, Andreas; Brandes, Axel; Eckardt, Lars; Elvan, Arif; Fetsch, Thomas; van Gelder, Isabelle C; Haase, Doreen; Haegeli, Laurent M; Hamann, Frank; Heidbüchel, Hein; et al. (The New England journal of medicine, 2020)
In this multicenter, randomized trial comparing early rhythm control with usual care in patients with early atrial fibrillation and cardiovascular conditions, early rhythm control reduced the rate of death from cardiovascular causes and cardiovascular complications and did not affect the number of nights in the hospital.